Empowering College Students Critical Thinking Skill Through Mathematic and Newspaper Literacies - Wahyuni, Molli (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
In this 21st century, Mathematic Literacy plays important roles in the world of mathematics education. Learners are expected to be mathematical literate and are able to understand and actualize it in real-life problems. The real-life problems of mathematics, for example the graphics of Economic Inflation, can be easily found in the on and offline newspapers. The newspapers literacy is expected to advocate to studentsâ mathematic literacy. Today, the mathematics is often abstractly valued so that it hardly affects the studentsâ ability to solve mathematic problems found in the real-life.This research is literatur research that studies, analysis, and concludes literatture. This paper will discuss about the relationship between Mathematic and Newspaper Literacies. Furthermore discuss how to the empowering college studens critical thinking skill trough mathematic and newspaper literacies.